An evaluation of the association between an antimicrobial stewardship score and antimicrobial usage. (21st January 2015) - Pakyz, Amy L.; Moczygemba, Leticia R.; Wang, Hui; Stevens, Michael P.; Edmond, Michael B.
Abstract: Objectives: To determine whether an antimicrobial stewardship 'intensity' score predicts hospital antimicrobial usage. Methods: An antimicrobial stewardship score for 44 academic medical centres was developed that comprised two main categories: resources (antimicrobial stewardship programme personnel and automated surveillance software) and strategies (preauthorization, audit with intervention and feedback, education, guidelines and clinical pathways, parenteral to oral therapy programmes, de-escalation of therapy, antimicrobial order forms and dose optimization). Multiple regression analyses were used to assess whether the composite score and also the categories were associated with either total or antimicrobial stewardship programme-target antimicrobial use as measured in days of therapy. Results: The mean antimicrobial stewardship programme score was 55 (SD 21); the total composite score was not significantly associated with total or target antimicrobial use [estimate –0.49 (95% CI –2.30 to 0.89)], while the category strategies was significantly and negatively associated with target antimicrobial use [–5.91 (95% CI –9.51 to –2.31)]. Conclusions: The strategy component of a score developed to measure the intensity of antimicrobial stewardship was associated with the amount of antimicrobials used. Thus, the number and types of strategies employed by antimicrobial stewardship programmes may be of particular importance in programme effectiveness.